Thyroid Hormones and Autoantibodies in Iraqi Hyperthyroid Patients - T. Al-Mofarji, Sarah; M. Jasim, Hameed; B. Mohammed, Sanad (Al-Nahrain Journal of Science, 2023)
Hyperthyroidism can be defined as the status of over production of thyroid hormones: tri-iodothyronine (T3) and thyroxine (T4) as a results of thyroid gland dysfunction. The aim of the current study was to investigate the association between the abnormalities of thyroid hormones (T3 and T4) and serum levels of thyroid auto-antibodies: anti-thyroid peroxidase (TPO-Ab) and anti-thyroid stimulating hormone receptor (TR-Ab) and the state of hyperthyroidism. Blood samples were collected from 75 Iraqi individuals were early diagnosed as hyperthyroidism patients in addition to 25 Iraqi individuals as a healthy control group. Enzyme Linked Fluorescent Assay (ELFA) used to determine the levels of thyroid hormones (T3 and T4) and the level of thyroid stimulating hormone (TSH), Enzyme Linked Immuno-Sorbent Assay (ELISA) was used to determine the levels of auto-antibodies (TPO-Ab and TR-Ab). The results show that T3 levels and T4 levels in hyperthyroidism patients (2.07 nmol/L and 14.02 µg/dl respectively) increased significantly  compared to healthy control levels (1.33 nmol/L and 6.4 µg/dl respectively). While the levels of thyroid stimulating hormone (TSH) in hyperthyroidism patient (0.17 µIU/Ml) decreased significantly  when compared with healthy control group (1.84 µIU/Ml). The results also showed that levels of TPO-Ab and TR-Ab in hyperthyroidism patients (235.29 IU/mL and 32.05 IU/mL respectively) increased significantly  when compared to healthy control group (20.76 IU/mL and 0.3 IU/mL respectively). This study revealed that there is an association between thyroid hormones disorders and the positivity of thyroid auto-antibodies in hyperthyroidism patients.